Visible-to-NIR-Light Activated Release: From Small Molecules to Nanomaterials - Weinstain, Roy; Slanina, Tomáš; Kand, Dnyaneshwar; Klán, Petr (Chemical reviews, 2020)
Photoactivatable (alternatively, photoremovable, photoreleasable, or photocleavable) protecting groups (PPGs), also known as caged or photocaged compounds, are used to enable non-invasive spatiotemporal photochemical control over the release of species of interest. Recent years have seen the development of PPGs activatable by biologically and chemically benign visible and near-infrared (NIR) light. These long-wavelength-absorbing moieties expand the applicability of this powerful method and its accessibility to non-specialist users. This review comprehensively covers organic and transition metal-containing photoactivatable compounds (complexes) that absorb in the visible- and NIR-range to release various leaving groups and gasotransmitters (carbon monoxide, nitric oxide, and hydrogen sulfide). The text also covers visible- and NIR-light-induced photosensitized release using molecular sensitizers, quantum dots, and upconversion and second-harmonic nanoparticles, as well as release via photodynamic (photooxygenation by singlet oxygen) and photothermal effects. Release from photoactivatable polymers, micelles, vesicles, and photoswitches, along with the related emerging field of photopharmacology, is discussed at the end of the review.